DIALOGUES ON FOOD IN THE FIRST YEAR OF LIFE: PROPOSAL OF AN EDUCATIONAL WORKSHOP AS HEALTHY FOOD INCENTIVE STRATEGY - Jane de Carlos Santana Capelli; Naiara Sperandio; Luana Silva Monteiro; Silvia Pereira; Thaina Lobato Calderoni; Rhaíssa Rocha Figueira; Fernanda Amorim de Morais Nascimento Braga (Universidade do Estado do Rio de Janeiro, 2019)
The aim of this paper is to analyze an educational workshop used as a food and nutrition education strategy to encourage adequate and healthy eating in the first year of life, with emphasis on complementary feeding. An educational workshop was conducted by two teams: one linked to an extension project known as IACOL; and another linked to the Center for Studies on Maternal and Women's Health and Feeding (NESAM). Conversation rounds - whose strategy is the construction of dialogic practice - were used. The following steps were followed: (a) Presentation of the teams; (b) Welcome; (c) Health/illness process; (d) Breastfeeding; (e) Introduction of complementary feeding; (f) Complementary feeding (in box); (g) Quiz; (h) Discussion of the topic and question & answer session; and (i) Evaluation of the educational workshop. The activity was attended by 64 participants: health workers and undergraduates from various fields of health. Regarding the knowledge acquired by the learners in the educational workshop, in the Quiz, which contained ten statements based on the "Ten Steps to Healthy Eating: Food Guide for Children Under Two Years Old," four statements had 100.0% of correct answers, and four others had percentages ranging from 45.1% to 62.5%. It should be noted that the statement relative to step 10 was the one that had the highest percentage of wrong answers (73.4%) by the learners, and another statement was annulled. The learners' evaluation was satisfactory in the global subjective assessment, based on interest, participation and frequency, for all stages. In conclusion, the educational activity provided the learners with knowledge about food in the first year of life; however, for some steps, the educational workshop will be redesigned. DOI: 10.12957/demetra.2019.43384